Clinical applications of molecular basis for Craniosynostosis. A narrative review. - Saúl Ernesto Cifuentes-Mendiola; Isaac Obed Pérez-Martínez; Ángel Enrique Muñoz-Saavedra (Universidad de Concepción., 2016)
Cranial sutures are specialized structures composed of the sutural mesenchyme, the overlying scalp, the dura and osteogenic fronts. Each one of these structures express important proteins for osteogenic maturation, membranous ossification of skull bones, and homeostasis of cranial sutures in a differential, spatial and temporal manner. These proteins include fibroblast growth factor (FGF) and its receptors (FGFR), the transforming growth factor beta (TGF-β), bone morphogenetic proteins (BMPs), as well as transcription factors TWIST and MSX2, among others. The alteration in the expression of one or more of these proteins causes multiple pathological conditions; one of them is the premature closure of one or more cranial sutures, known as craniosynostosis. This malformation is commonly treated with surgery. However, advances in the fields of molecular and cellular biology have allowed to conduct research on some proteins involved in the development of craniosynostosis. The results of these studies can lead to future preventive therapeutic strategies that may be used as a complement to the surgical treatment of craniosynostosis. Possible strategies include the use of specific drugs that can regulate the expression and activation of FGF signaling pathways, TGF-β or BMPs, to prevent or avoid craniosynostosis or re-synostosis after a surgery.